Respostas
respondido por:
12
17x - 1 = 15x + 3
17x - 15x = 3 + 1
2x = 4
x = 4/2
×=2
:) espero ter ajudado
17x - 15x = 3 + 1
2x = 4
x = 4/2
×=2
:) espero ter ajudado
respondido por:
3
PRIMEIRO PASSO ORGANIZAR A EQUAÇÃO:
se era 17x -1 = 15x +3 vai ficar:
17x - 15x = +3 +1 aí é só resolver:
2x = +4
x = 4 dividido pra 2
x = 2
espero ter ajudado!
se era 17x -1 = 15x +3 vai ficar:
17x - 15x = +3 +1 aí é só resolver:
2x = +4
x = 4 dividido pra 2
x = 2
espero ter ajudado!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás